Editorial - Amana Mattos; Ana Maria Jacó-Vilela; Deise Maria Fernandes Mendes; Heloisa Fernandes Caldas Ribeiro; Jimena de Garay Hernández; Laura Cristina de Toledo Quadros; Patrícia Lorena Quitério; Vanessa Barbosa Romera Leme (Estudos e Pesquisas em Psicologia, 2020)
Amana Mattos, Ana Maria Jacó Vilela, Deise Maria Fernandes Mendes, Heloisa Fernandes Caldas Ribeiro, Jimena de Garay Hernández, Laura Cristina de Toledo Quadros, Patrícia Lorena Quitério, Vanessa Barbosa Romera Leme